First successful hand-rearing and release to the wild of two orphan brown bear cubs in Greece - KOMNENOU, A. Th.; KARAMANLIDIS, A. A.; KAZAKOS, G. M.; KYRIAZIS, A. P.; AVGERINOU, M.; PAPAKOSTAS, G.; STEFANIDIS, K.; BEECHAM, J. J. (Journal of the Hellenic Veterinary Medical Society, 2018)
The rehabilitation and release of orphan brown bears (Ursus arctos) to the wild is of increasing importance in the conservation and management of the species. In April 2011 two orphan male brown bears were found and rehabilitated for the first time at a dedicated Bear Rehabilitation Centre in Greece. In this case report we describe in detail the veterinary procedures and the feeding regime followed during the 9-month rehabilitation process. For the release on the 23rd of January 2012 the two bears were anaesthetized with a combination of xylazine and ketamine, and satellite collars were placed on them for post-release monitoring. Eight hours later the bears were anaesthetized with the same mixture for a second time, transported and placed into an artificial den in the wild; recovery from anaesthesia took place without complications. Three months later the bears left the den and started moving in the wider area of northwestern Greece. We conclude that rehabilitation and release of orphan bears is an important tool in the management and conservation of this endangered species in Greece.